Politik demokrasi penaungan dalam politik kenyah di Sarawak : kajian kes di Long San semasa pilihan raya negeri Sarawak 2011 - Jeffrey, Ngau Lenjau (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The politics of patronage democracy is referring to the allocation of state resources to his staunch supporters such as timber concession, job vacancies in government and many more. In return, his loyal supporters must vote for him in the elections. However, politics of patronage democracy politics also brings great impact toward class societies practicing social stratification systems. This research was unique because the level of analysis was used combination between anthropology and political science approach. At the same time, this research also analysis politics of patronage democracy from grass root perspective. The social stratification system means the differences between two different groups of people based on their social status towards their everyday social interactions. Kenyah community from Long San, Baram, Miri, in Sarawak (Malaysia) provides a good example for this study by showing the implication of patronage democracy politics on Kenyah society. To clarify the existence of politics of patronage democracy politics in Kenyah politics, this study took the 2011 Sarawak state election as a case study. Researcher used in depth interview, unstructured interview, participant observation, case studies and genealogy system technique from aristocrat class perpective as tool of colleting data. This thesis has two research objectives which include; (1), to determine if social stratification influences contemporary Kenyah political structure; and (2), to access the impact of politics of patronage democracy upon Kenyah solidarity. Moreover, the gaps between the keta’u (aristocrat) and the panyen (commoner) become wider and obvious from politic of patronage democracy contexts. Apart from that, this study found that the Kenyah society today is divided into two main blocks of social classes which are the panyen and keta'u. The fragmentation of Kenyah society is clearly shown in their different of political ideologies.